2021
DOI: 10.3390/jcm11010120
|View full text |Cite
|
Sign up to set email alerts
|

Canonical (CD74/CD44) and Non-Canonical (CXCR2, 4 and 7) MIF Receptors Are Differentially Expressed in Rheumatoid Arthritis Patients Evaluated by DAS28-ESR

Abstract: Macrophage migration inhibitory factor (MIF) significantly contributes to rheumatoid arthritis (RA) pathogenesis. We aimed to evaluate the canonical (CD74/CD44) and non-canonical MIF receptors (CXCR2,4 and 7) expression and sCD74 to establish their association with RA clinical activity according to DAS28-ESR. Methodology: 101 RA patients with different clinical activities (remission (n = 27), low (n = 16), moderate (n = 35) and high (n = 23)) and 9 control subjects (CS) were included. Expression was evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…A high expression of MIF mRNA and protein in human autoimmune-associated kidney disease was described over 20 years ago by Lan et al [65]. Both CD74 and MIF have been extensively studied in the context of rheumatoid arthritis, and MIF is now recognized as a crucial player in the development of this disease [66][67][68][69]. Recently, therapeutics aimed at disrupting MIF and/or CD74 binding have been considered in the treatment of several autoimmune diseases [64,70,71].…”
Section: A Brief Overview Of Mif and Cd74mentioning
confidence: 99%
“…A high expression of MIF mRNA and protein in human autoimmune-associated kidney disease was described over 20 years ago by Lan et al [65]. Both CD74 and MIF have been extensively studied in the context of rheumatoid arthritis, and MIF is now recognized as a crucial player in the development of this disease [66][67][68][69]. Recently, therapeutics aimed at disrupting MIF and/or CD74 binding have been considered in the treatment of several autoimmune diseases [64,70,71].…”
Section: A Brief Overview Of Mif and Cd74mentioning
confidence: 99%
“…In addition, CD74 and NOTCH3 exhibited the highest positive or negative correlation with HLA-DRB1/DMB, respectively. CD74 is a membrane protein mainly distributed on the surface of immune cells, which transduces signals by binding to MIF (Sánchez-Zuno et al, 2021), while HLA-DRB1 sharesepitope sequences that mainly encode antigen presentation proteins and contribute to ACPA-positive RA (Kampstra and Toes, 2017). The positive correlation between the two may reflect the degree of immune cell-mediated autoimmune inflammation.…”
Section: Figure 10mentioning
confidence: 99%
“…Alternatively, MIF ligation of CD74 can lead to regulated intramembrane proteolysis (RIP) and the release of an intracellular domain (ICD) of CD74 that has a nuclear trafficking capacity, acts as a transcription factor, and can activate NF‐κB 138–141 . In turn, the liberated soluble CD74 ectodomain has been found to serve as a circulating scavenger to neutralize MIF‐elicited signaling responses and its plasma levels have been (inversely) associated with disease progression 118,119,142–145 . How soluble CD74 regulates MIF‐2 activity is poorly understood, but initial studies have observed correlations between soluble CD74 plasma levels and disease activity in burn and cardiac surgery patients 145,146 .…”
Section: Receptors and Signaling Pathways Instigated By Mif‐2 And Com...mentioning
confidence: 99%
“…[138][139][140][141] In turn, the liberated soluble CD74 ectodomain has been found to serve as a circulating scavenger to neutralize MIF-elicited signaling responses and its plasma levels have been (inversely) associated with disease progression. 118,119,[142][143][144][145] How soluble CD74 regulates MIF-2 activity is poorly understood, but initial studies have observed correlations between soluble CD74 plasma levels and disease activity in burn and cardiac surgery patients. 145,146 The cardio-and hepatoprotective activities of the MIF/CD74 axis in the ischemic heart and during hepatic fibrosis, respectively, involve signaling through the metabolic stress enzyme AMP-activated protein kinase (AMPK) as well as Jun kinase (JNK) pathways.…”
Section: Pathways Instigated By Mif-2 and Comparison To Mifmentioning
confidence: 99%